2016
DOI: 10.1039/c5cp05699c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic performance of an Ag3PO4photocatalyst via fullerene modification: first-principles study

Abstract: The coupling of carbon nanomaterials with semiconductor photocatalysts is a promising route to improve their photocatalytic performance. Herein, density functional theory was used to investigate the electronic structure, charge transfer, photocatalytic activity, and stability in a series of hybrid fullerene (C20, Li@C20, C26, Li@C26)/Ag3PO4(100) composites. When a Li atom is incorporated in fullerene, the adsorption energies significantly increase, although the change of interface distance is negligibly small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…In addition, a type‐II staggered band alignment, which was formed in the MoS2/C20 and WS2/fullerenes heterostructures, contributed to the enriched photocatalytic performance and the reduced charge recombination. Fullerene modification was found to be a useful approach to enhance the photoactivity of Ag 3 PO 4 via plane wave DFT/LDA + U approach implemented in CASTEP code . The U parameters of 7.2, 7.0, and 7.0 eV was used for the Ag 4d, O 2p, and P 3p states, respectively.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In addition, a type‐II staggered band alignment, which was formed in the MoS2/C20 and WS2/fullerenes heterostructures, contributed to the enriched photocatalytic performance and the reduced charge recombination. Fullerene modification was found to be a useful approach to enhance the photoactivity of Ag 3 PO 4 via plane wave DFT/LDA + U approach implemented in CASTEP code . The U parameters of 7.2, 7.0, and 7.0 eV was used for the Ag 4d, O 2p, and P 3p states, respectively.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In this context, using boron cluster to noncovalently modify Ag 3 PO 4 or other semiconductor photocatalysts could improve their photocatalytic activity and stability, as has been demonstrated by its analogue carbon cluster (i.e., C 60 ). 37 3.5. Optical Properties.…”
Section: Interaction Potential Energy and Formsmentioning
confidence: 99%
“…When C 60 was covered on ZnO, the activity of surface oxygen atoms was effectively reduced so that photocorrosion effect was effectively inhibited. Similarly, high stabilization of AgPO 4 /C 60 was also observed, because C 60 could obviously suppress the transform of Ag + into Ag of bare Ag 3 PO 4 composite [ 6 ]. Moreover, Cai, et al [ 43 ] fabricated CdS/C 60 nanocomposite in which C 60 has shown effectively inhibition of photocorrosion of CdS.…”
Section: Role Of Fullerenementioning
confidence: 99%
“…Since the photocatalytic performance of TiO 2 for water splitting was proposed for the first time by Fujishima and Honda in 1970s, much work has been done to study the photocatalytic mechanisms and develop novel photocatalysts [3]. Up to date, numerous appealing photocatalysts have been developed and extensively investigated, such as simple oxides (ZnO) [4], metal chalcogenides (CdS) [5], Ag-based compound (Ag 3 PO 4 ) [6], Bi-based compound (BiVO 4 and Bi 2 MoO 6 ) [7,8], MOFs [9] and g-C 3 N 4 [10]. In addition to novel photocatalysts, cocatalysts such as presence of electron donors such as ethylenediamine tetraacetic acid (EDTA) and nicotinamide adenine dinucleotide (NADH) [22].…”
Section: Introductionmentioning
confidence: 99%